Human salivary protein-derived peptides specific-salivary SIgA antibodies enhanced by nasal double DNA adjuvant in mice play an essential role in preventing Porphyromonas gingivalis colonization: an in-vitro study - Kayo Koyanagi; Kosuke Kataoka; Hideki Yoshimatsu; Kohtaro Fujihashi; Tatsuro Miyake (BMC, 2023)
Abstract Background We previously showed that fimbriae-bore from Poryphyromonas gingivalis (Pg), one of the putative periodontopathogenic bacteria specifically bound to a peptide domain (stat23, prp21) shared on statherin or acidic proline-rich protein 1 (PRP1) molecule of human salivary proteins (HSPs). Here, we investigated whether the nasal administration of DNA plasmid expressing Flt3 ligand (pFL) and CpG oligodeoxynucleotide 1826 as double DNA adjuvant (dDA) with stat23 and prpr21 induces antigen (Ag)-specific salivary secretory IgA (SIgA) antibodies (Abs) in mice. Further, we examined that stat23- and prpr21-specific salivary SIgA Abs induced by dDA have an impact on Pg-binding to human whole saliva-coated hydroxyapatite beads (wsHAPs). Material and methods C57BL/6N mice were nasally immunized with dDA plus sta23 or/and prp21 peptide as Ag four times at weekly intervals. Saliva was collected one week after the final immunization and was subjected to Ag-specific ELISA. To examine the functional applicability of Ag-specific SIgA Abs, SIgA-enriched saliva samples were subjected to Pg binding inhibition assay to wsHAPs. Results Significantly elevated levels of salivary SIgA Ab to stat23 or prp21 were seen in mice given nasal stat23 or prp21 with dDA compared to those in mice given Ag alone. Of interest, mice nasally given the mixture of stat23 and prp21 as double Ags plus dDA, resulted in both stat23- and prp21-specific salivary SIgA Ab responses, which are mediated through significantly increased numbers of CD11c+ dendritic cell populations and markedly elevated Th1 and Th2 cytokines production by CD4+ T cells in the mucosal inductive and effector tissues. The SIgA Ab-enriched saliva showed significantly reduced numbers of live Pg cells binding to wsHAPs as compared with those in mice given double Ags without dDA or naïve mice. Additionally, saliva from IgA-deficient mice given nasal double Ags plus dDA indicated no decrease of live Pg binding to wsHAPs. Conclusion These findings show that HSP-derived peptides-specific salivary SIgA Abs induced by nasal administration of stat23 and prp21 peptides plus dDA, play an essential role in preventing Pg attachment and colonization on the surface of teeth, suggesting a potency that the SIgA may interrupt and mask fimbriae-binding domains in HSPs on the teeth.